Overtaking as Indicator of Road Traffic Conditions - Topolnik, Dražen; Zebec, Zoran; Horvat, Rajko (Promet - Traffic&Transportation, 2012)
Overtaking is presemed as one of the indicators of roadtraffic flow. The possibility of overtaking depends on the existenceof an intetval in the opposing traffic flow sufficient to performovertaking. It also analyses the probability of overtakingby applying adequate equations and graphical presentations